Consider Military Junta’s Order to Ban of Political Gatherings as State Repression in Thailand - Archamas, Noppon (CMU Journal of Law and Social Sciences, 2019)
This article considered Thai military junta orders to ban political gatherings of five or more people as a state repression tool. It aimed to investigate the development and change of the orders of different Thai military juntas to reveal the continuity of utilization of this tool for power control after each coup and criminalization of the freedom of assembly so that this became a normal practice after each military coup. This article also considered the enforcement of this order under the administration of the National Council for Peace and Order (NCPO), when the order was the most intensively enforced when compared with previous coups. This showed their goal of applying this order, which became a law on suppressing the opposition to the coup, controlling the assembly against the military junta’ power exercising and administration, prohibiting or intervening in public activities, and creating burdens or costs in relation to expressions for activists or politically-active citizens.